(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
International distribution of goods is the process of promoting the goods from manufacturer through trading enterprises and other intermediaries to buyers, each of whom is a representative of a foreign (in relation to another participant) states. The logistics system is a system for bringing the material flow to the consumer. The following article is devoted to the logistics system for ensuring international commodity circulation.